Kansas PRIDE 2014-15 Program Recognition - Rice, Trudy; Menon, Jaime (My University, 2015)
Summary of the 2014-2015 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development